Health Insurance Coverage and Income Uncertainty - Swarn Chatterjee (ZBW - Leibniz Information Centre for Economics, 2009)
This paper uses the National Longitudinal Survey data set to examine the role of income uncertainty in explaining the likelihood of health insurance coverage among individuals. After controlling for a number of socioeconomic, demographic, and behavioral factors, the results suggest that individuals who face greater income uncertainty are less likely to have health insurance coverage. Additionally, the likelihood of health insurance coverage increases with income and educational attainment.
Keywords: D10; D14; I13; I18; 330; Health Insurance; Pre-Obamacare; Income Uncertainty; Health